Expression in A. thaliana and cellular localization reveal involvement of BjNRAMP1 in cadmium uptake - Li, Ting; Li, Yicun; Wang, Jiaqi; Peng, Jiashi; Liu, Lili; Deng, Lichao; Zhang, Dawei; Yan, Mingli (Frontiers in Plant Science, 2023)
Although Brassica juncea has demonstrated potential as a hyperaccumulator crop, it was not entirely clear how cadmium (Cd) accumulates in plants. Here, we found that BjNRAMP1 (Natural Resistance-Associated Macrophage Protein 1) plays a crucial role in the accumulation of Cd and manganese (Mn) through its expression in yeast and Arabidopsis thaliana. The high concentration of Cd exposure could induce the expression of BjNRAMP1. The ectopic expression of BjNRAMP1 in yeast led to higher accumulation of Cd and Mn compared to the vector control. BjNARAMP1 was localized to the plasma membrane and expressed in the vascular system of roots, leaves, and flowers. The overexpression of BjNRAMP1 in A. thaliana resulted in an increased accumulation of Cd in both roots and shoots, which inhibited the normal growth of transgenic lines. Moreover, Mn uptake in roots was activated by the increase in Cd stress. Together, our results indicated that BjNRAMP1 significantly contributes to the uptake of Mn and Cd in B. juncea.